2004
DOI: 10.1161/01.cir.0000133322.19340.ef
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurements of Crossbridge Dynamics and Lattice Spacing in Rat Hearts by X-Ray Diffraction

Abstract: Background-Synchrotron radiation has been used to analyze crossbridge dynamics in isolated papillary muscle and excised perfused hearts with the use of x-ray diffraction techniques. We showed that these techniques can detect regional changes in rat left ventricle contractility and myosin lattice spacing in in situ ejecting hearts in real time. Furthermore, we examined the sensitivity of these indexes to regional ischemia. Methods and Results-The left ventricular free wall of spontaneously beating rat hearts (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
(31 reference statements)
4
27
1
Order By: Relevance
“…Such a mechanism can explain the abrupt transitions that we observed in myofilament calcium sensitivity, I 1,1 /I 1,0 intensity ratio, and interfilament spacing at low levels of applied osmotic compression. A difficulty with this view, however, is that it conflicts with recent studies (30,39) that measured myofilament lattice spacing and I 1,1 /I 1,0 intensity ratio in whole hearts. Both studies reported a diastolic (relaxed) I 1,1 /I 1,0 intensity ratio of ϳ0.4, equivalent to the compressed patterns we observed in the skinned fibers, but the reported myofilament lattice spacing was very different between the two studies: ϳ42 nm (30) and ϳ37.5 nm (39).…”
Section: Osmotic Pressure Sensitive Switch For Calcium Sensitivity?mentioning
confidence: 74%
“…Such a mechanism can explain the abrupt transitions that we observed in myofilament calcium sensitivity, I 1,1 /I 1,0 intensity ratio, and interfilament spacing at low levels of applied osmotic compression. A difficulty with this view, however, is that it conflicts with recent studies (30,39) that measured myofilament lattice spacing and I 1,1 /I 1,0 intensity ratio in whole hearts. Both studies reported a diastolic (relaxed) I 1,1 /I 1,0 intensity ratio of ϳ0.4, equivalent to the compressed patterns we observed in the skinned fibers, but the reported myofilament lattice spacing was very different between the two studies: ϳ42 nm (30) and ϳ37.5 nm (39).…”
Section: Osmotic Pressure Sensitive Switch For Calcium Sensitivity?mentioning
confidence: 74%
“…By exposing a finely collimated SR X-ray beam (dimensions, 0.2×0.2 mm) to the whole heart, it is now possible to record the diffraction peaks in a myocardial region without averaging over multiple heart beats at a time resolution of 15 to 20 ms. [78][79][80] The time resolution is not limited by the available flux but mainly by radiation damage. Studies of a whole heart started with the isolated rat heart.…”
Section: Current and Past Saxs Studies From Myocytes To The In Situ Hmentioning
confidence: 99%
“…This initial study showed that the interfilament spacing does not differ significantly at different layers of the wall. 80 Studies of an isolated rat heart have expanded to more physiological studies of an open-chest in situ rat heart 78,79 and a closed-chest mouse heart. 81 The open-chest heart preparation allows the researcher to investigate regional differences in cross-bridge dynamics, because the myocardial regions exposed to the beam can be determined.…”
Section: Current and Past Saxs Studies From Myocytes To The In Situ Hmentioning
confidence: 99%
“…Diffraction patterns were recorded for time resolved studies in isolated perfused hearts [24] and in situ [25]. Results suggest that it is possible to assign the origin of reflections in the diffraction diagram from the whole heart [24].…”
Section: Small-angle Diffractionmentioning
confidence: 99%
“…Results suggest that it is possible to assign the origin of reflections in the diffraction diagram from the whole heart [24]. Moreover, X-ray diffraction techniques permit real-time in situ analysis of regional crossbridge dynamics at the molecular and fiber levels for examination of regional ischemia [25].…”
Section: Small-angle Diffractionmentioning
confidence: 99%